Blue jeans : the art of the ordinary - Miller, Daniel, 1954-; Woodward, Sophie (University of California Press, 2012)
This fresh and accessible ethnography offers a new vision of how society might cohere, in the face of on-going global displacement, dislocation, and migration. Drawing from intensive field work in a highly diverse North London neighborhood, Daniel Miller and Sophie Woodward focus on an everyday item--blue jeans--to learn what one simple article of clothing can tell us about our individual and social lives and challenging, by extension, the foundational anthropological presumption of "the normative." Miller and Woodward argue that blue jeans do not always represent social and cultural difference.